Bypass of Primary Stroke Centers Compared With Secondary Transfer for Endovascular Thrombectomy - Jae Beom Hong; William K. Diprose; Michael T. M. Wang; Juliette Meyer; Dean Kilfoyle; Stefan Brew; Peter Alan Barber (Stroke: Vascular and Interventional Neurology, 2022)
Background Our stroke network operates a hybrid organizational structure, with patients with potential large‐vessel occlusion taken to the local primary stroke center (PSC) during office hours, and directly bypassed to the endovascular thrombectomy–capable stroke center (EVT‐SC) after hours. We aimed to compare the 2 methods of transfer. Methods Consecutive patients with anterior large‐vessel occlusion treated with EVT between August 2017 and February 2021 were identified. Patients who had EVT puncture within 6 hours of last known normal were included for analysis. Patients were grouped into method of presentation: direct bypass to EVT‐SC (“EVT‐SC direct”) or taken to local PSC with secondary transfer to EVT‐SC (“PSC‐transfer”). The primary outcome was 3‐month functional independence (modified Rankin scale score 0–2). Secondary outcomes included mortality at 7 days and at 3 months. Results A total of 259 patients (109 women; mean±SD age, 66.8±15.2 years) were included; there were 91 (35.1%) EVT‐SC direct and 168 (64.9%) PSC‐transfer patients. The EVT‐SC direct patients had shorter median times from last known normal to thrombolysis (120 versus 147 minutes; P=0.004) and puncture (190 versus 230 minutes; P<0.001). Multivariable logistic regression analysis found that EVT‐SC direct patients had greater 3‐month functional independence (odds ratio [OR], 2.04 [95% CI, 1.12–3.73]; P=0.02) and lower 3‐month mortality (OR, 0.33 [95% CI, 0.12–0.91]; P=0.03). For every 100 patients directly bypassed to EVT‐SC, there were 14 more patients functionally independent and 9 fewer who had died, at 3 months. Conclusions In this comparison of 2 organizational paradigms in patients with a PSC as the closest stroke center, direct bypass to EVT‐SC resulted in significantly better process times and clinical outcomes compared with secondary transfers from PSCs.